Prognostic effect of pretreatment serum gamma-glutamyl transferase in urological malignancies: a systematic review and meta-analysis - Song, Feifan; Su, Shiqiang; Zhang, Xueqiao; Cui, Xiongjie; Li, Chao; Li, Shen (Frontiers in Oncology, 2025)
BackgroundThis study aimed ​​to investigate​​ the association between pretreatment serum gamma-glutamyltransferase (GGT) and survival outcomes in patients with urological malignancies, such as urothelial carcinoma (UCa), renal cell carcinoma (RCC), and prostate cancer (PCa).MethodsA comprehensive literature search was conducted in PubMed, Ovid, Web of Science, and the Cochrane Library up to December 2024. Survival outcomes were analyzed through the computation of merged hazard ratios (HRs) and 95% confidence intervals (CIs) using Stata 18.0 software.ResultsTen studies involving 2,817 patients were included in the final analysis. The results indicated that elevated pretreatment serum GGT demonstrated a significant association with poorer overall survival (OS) (HR = 3.32, 95% CI: 2.51-4.39), cancer-specific survival (CSS) (HR = 1.95, 95% CI: 1.26-3.04), and progression-free survival (PFS) (HR = 2.34, 95% CI: 1.72-3.17). Subgroup analyses stratified by cancer type demonstrated that elevated serum GGT served as a significant predictor of OS in UCa (HR 3.11, 95% CI 2.08-4.65), RCC (HR 3.51, 95% CI 2.27-5.43), and PCa (HR 3.61, 95% CI 1.51-8.62). Consistent associations were observed for CSS (Uca: HR 1.88, 95% CI 1.23-2.88) and PFS (Uca: HR 2.58, 95% CI 1.24-3.93; RCC: HR 2.00, 95% CI 1.28-3.13; PCa: HR 2.90, 95% CI 1.34-6.26). No significant publication bias was detected across the included studies.ConclusionsPretreatment serum GGT served as an independent predictor of OS, CSS, and PFS in urological malignancies, suggesting that it may be a potential prognostic factor in clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025629976, identifier CRD42025629976.